Associations Between Energy and Fat Intakes with Adiposity in Schoolchildren – the Cuenca Study [Asociación Entre la Ingesta Energética y de Grasas y la Adiposidad en Escolares - Estudio Cuenca] - Garcia-Hermoso, A (Grupo Aula Medica S.L., 2015)
Introduction: the relationship between changes in energy intake (EI) over the last few decades and the trends towards of excess weight in children is still debated. Objective: to examine the relationship between energy and macronutrient intakes with adipostity in children, controlling for cardiorespiratory fitness (CRF) as a surrogate measure of physical activity. Method: we conducted a cross-sectional study of 320 schoolchildren aged 9-11 years (54.5% girls). We collected data on socio-demographic variables, and measured weight, height, waist circumference (WC), and fat mass percentage by bioimpedance analysis. Fat mass index (FMI) was calculated as fat mass (kg) divided by height (m) squared, to adjust for body size. Energy (kcal) and macronutrient intake (percentages) were measured by two non-consecutive 24-h recalls (weekday and weekend day), using the Young Adolescents’ Nutrition Assessment on Computer (YANA-C) software program; CRF was measured by the 20-m shuttle run test. Results: boys in the 4th quartile of the WC distribution had lower fat intake (34.9%) than boys in the 1st (42.4%; p = 0.019) and 2nd quartiles (41.6%; p = 0.022). Children in the 1st quartile of the FMI distribution had higher daily EIs than children in the 4th quartile (1762.3 kcal vs. 1496.8 kcal; p = 0.023). All macronutrient intakes relative to weight were lower in children in the more adipose categories for weight status, WC and FMI (p < 0.001). Conclusion: adiposity was inversely related to energy and fat intakes. Excessive EI and high EI from fats not appears to be directly associated with the current obesity epidemic among schoolchildren living in Cuenca (Spain). © 2015, Grupo Aula Medica S.A. All Rights Reserved.